Universalisme Islam Cosmopolitan Di Indonesia Dalam Prespektif Gus Dur Dan Cak Nur - Hunain, Ishaq; Qomariyah, Fitriyatul; Ramadhana, Maghfiroh; Kamil, Moh (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2024)
Abstract Indonesia is a multicultural country with various cultures, ethnicities, languages and religions. Islam is the religion with the most followers in Indonesia. In this case, there are many Muslim leaders in Indonesia who have different perspectives, so that an understanding of cosmopolitan Islamic universalism emerges in Indonesia, in which one of the characters is Nurcholis Madjid and Abdurrahman Wahid. This article will discuss the thoughts of the two figures in cosmopolitan Islamic universalism. The research method used in this research is a library research with the main sources being books, articles and relevant journals. The results of this study are that Islamic universalism according to Gus Dur is divided into three concepts of thought, the first being pluralism, democracy and indigenization. As for Cak Nur's thoughts, he views Islam as Cosmopolitan Universalism in line with Gus Dur's thoughts, which views Islam as a religion of rahmatal lil alamin which rejects the caliphate system because according to both of them what we need to echo is the value of Islam in life in society. Keywords: Universalisme Islam Cosmopolitan, Abdurrahman Wahid, Nurcholis Madjid Abstrak Indonesia merupakan negara multicultural dengan beragam budaya, suku, Bahasa dan agama. Agama Islam merupakan agama dengan pemeluk terbanyak di Indonesia. Dalam hal ini banyak tokoh muslim di Indonesia yang memiliki perspektif yang berbeda-beda, hingga muncullah pemahaman tentang universalisme Islam cosmopolitan di Indonesia, yang mana salah satu tokohnya adalah Nurcholis Madjid dan Abdurrahman Wahid. Artikel ini akan membahas tentang pemikiran kedua tokoh tersebut dalam universalisme Islam cosmopolitan. Adapun metode penelitian yang digunakan dalam penelitian ini adalah library reseach dengan sumber utama berupa buku, artikel dan jurnal yang relevan. Adapun hasil dari penelitian ini adalah universalisme Islam menurut gus Dur terbagi dalam tiga konsep pemikiran yang pertama pluralisme, demokrasi dan pribumisasi. Adapun dalam pemikiran Cak Nur memandang Islam Universalisme Cosmopolitan selaras dengan pemikiran Gus Dur yang memandang Islam sebagai agama rahmatal lil alamin yang menolak system khilafah karena menurut keduanya yang perlu kita gaungkan adalah nilai Islam dalam kehidupan ditengah masyarakat. Kata Kunci: Universalisme Islam cosmopolitan, abdurrahman wahid, Nurcholis Majid